RENCANA PELAKSANAAN PEMBELAJARAN MATEMATIKA DI SEKOLAH MENENGAH KEJURUAN - Ai Tusi Fatimah; Asep Amam (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
This study aims to describe the lesson plan in vocational high schools. The analysis of lesson plan is based on: (1) conformity with the principles of lesson plan formulation in regulation of education and culture minister No. 22 of 2016 about standard of basic and intermediate education process; (2) conformity with the characteristics of learners, vocational mathematics knowledge, and learning activities in vocational education. Based on the analysis, it is necessary to develop lesson plan of vocational high schools tailored to the needs of learners and vocational mathematics knowledge in the work in the field of expertise both contextually and practically which will have implications for the design of mathematics tasks. Keywords:  Lesson Plan, Mathematics, Vocational